Employee Performance Analysis Along Work From Home During The Covid-19 Pandemic - Fitria Marisya; Hatidah Hatidah; Marsinah Marsinah; RA Rodia Fitri (Citakonsultindo, 2023)
The study's goal was to examine the impact of work environment and workload on employee performance mediated by work motivation along During the COVID-19, work from home at Department of Manpower and Transmigration, North Musi Rawas Regency, North Sumatra, South Indonesia Sample of the study was all employees and partners of the Manpower and Transmigration Office of North Musi Rawas Regency as many as 109 people. Data is analyzed using Structural Equation Modeling (SEM) analysis which is run through the AMOS 24 program. The findings of the study that was conducted prove simultaneously that workload, motivation at work, and the workplace environment all significantly and favorably affect performance., which partially each variable performance is impacted by workload, job motivation, and work environment., but work motivational factors have very dominant impact on the performance of the workforce, while Work motivation is significantly and favorably impacted by the workplace and workload. This proves that work motivation is a very important mediating variable in improving the employee's performance during the COVID-19 pandemic by working at home